Seroprevalence of Encephalitozoon cuniculi in Pet Rabbits at Animal Hospitals and Meat Rabbits at Slaughterhouse in Thailand - Jala, Siriluk; Sanyathitiseree, Pornchai; Lertwatcharasarakul, Preeda; Kovitvadhi, Attawit (Journal of Mahanakorn Veterinary Medicine, 2022)
In numerous countries, an epidemic of Encephalitozoon cuniculi (E. cuniculi) has been recorded in pet and meat rabbits. Therefore, the goal of this survey is to look into the seroprevalence and influencing factors of E. cuniculi antibodies in pet rabbits from Kasetsart University Veterinary Teaching Hospital during 2017-2021 (n=288) and meat rabbits from a slaughterhouse in Kanchanaburi province (n=142) between June and August 2020. An ELISA commercial test kit was used to detect antibodies against E. cuniculi. According to the findings of this study, E. cuniculi seroprevalence in pet and meat rabbits was 67.1 and 70.4%, respectively. The presence of antibodies against E. cuniculi in pet rabbits did not correspond with sex, age, or clinical symptoms (P>0.05). Meat rabbit farms in Sukhothai, Kanchanaburi, Phetchaburi, and Ratchaburi provinces, which send meat rabbits to the examined slaughterhouse, had seroprevalences of 81.3, 78.0, 64.0, and 30.0, respectively. There was statistically significant seroprevalence between these provinces (P=0.01). According to the findings, Thailand has a significant seroprevalence of E. cuniculi. As a result, a control and preventive program might be implemented in order to reduce the prevalence. Furthermore, the seroprevalence research might be extended in order to evaluate the situation and collect data for future planning.